Molecular mechanisms of the development of atrial fibrillation in patients with type 2 diabetes mellitus: prognostic role of biomarkers of fibrosis and inflammation - V. A. Ionin; E. I. Barashkova; A. M. Ananev; V. A. Pavlova; E. L. Zaslavskaya; E. I. Baranova (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2022)
The objective was to determine the concentrations of biomarkers of fibrosis and inflammation in the blood, parameters characterizing heart remodeling in patients with atrial fibrillation (AF) in combination with type 2 diabetes mellitus (T2DM).Methods and materials. The study included 231 examined patients aged 35 to 65 years: patients with DM (n=99), of which 49 patients with AF, and the comparison group consisted of patients with AF without T2DM (n=54) and healthy examined patients (n=78).Results. It was found that the concentration of profibrogenic biomarkers circulating in the blood of patients with AF and T2DM is higher than in patients with AF without T2DM: galectin-3 (13.4 (9.1–16.9) and 6.8 (4.6–12.8) ng/ml, p<0.001), TGF-beta1 (3032.5 (2468.5–4283.5) and 2339.7 (1813.3–3368.8) pg/ml, p=0.01), GDF-15 (2359.3 (1234.3–3465.1) and 1256.7 (889.9–2083.7) pg/ml, p><0.001), PINP (3625.4 (2462.1–4463.7) and 2451.3 (1842.0–2941.0) pg/ml, p><0.001) and PIIINP (92.8 (68.6–122.4) and 67.6 (47.9–93.3) ng/ml, p><0.001). Concentrations of proinflammatory cytokines CRP (3.5 (2.2–4.4) and 2.7 (1.4–7.1) mg/l, p=0.01) and CT-1 (1032.1 (667.6–1495.3) and 549.1 (411.9–960.1) pg/ml, p><0.001) in patients with AF and T2DM is higher than in patients with T2DM without AF. The levels of TNF-alpha, IL-6 in patients with AF and T2DM are comparable to the concentrations of these biomarkers of inflammation in patients with T2DM without AF. According to the results of echocardiography, it was revealed that the thickness of the epicardial adipose tissue in patients with AF and T2DM is greater than in patients with AF without T2DM and greater than in patients with T2DM without AF (7.1±0.4, 4.5±0.3 and 5.1±0.3, respectively, p><0.001). A strong positive correlation between GDF-15 and HbA1c was established according to the correlation analysis (r=0.617, p><0.0001) and regression analysis (β=0.586, p><0.0001). According to binomial logistic regression, it was found that T2DM in the examined cohort increased the risk of AF by 2.2 times (OR=2.2, 95 %CI 1.41–3.31, p=0.00004). Conclusion. The obtained new data on the increase in the concentration of profibrogenic factors in patients with AF in combination with T2DM indicate an important role of the formation of myocardial fibrosis in the development of this arrhythmia in these patients. Keywords: biomarkers, fibrosis, inflammation, atrial fibrillation, diabetes mellitus>˂0.001), TGF-beta1 (3032.5 (2468.5–4283.5) and 2339.7 (1813.3–3368.8) pg/ml, p=0.01), GDF-15 (2359.3 (1234.3–3465.1) and 1256.7 (889.9–2083.7) pg/ml, p˂0.001), PINP (3625.4 (2462.1–4463.7) and 2451.3 (1842.0–2941.0) pg/ml, p˂0.001) and PIIINP (92.8 (68.6–122.4) and 67.6 (47.9–93.3) ng/ml, p˂0.001). Concentrations of proinflammatory cytokines CRP (3.5 (2.2–4.4) and 2.7 (1.4–7.1) mg/l, p=0.01) and CT-1 (1032.1 (667.6–1495.3) and 549.1 (411.9–960.1) pg/ml, p˂0.001) in patients with AF and T2DM is higher than in patients with T2DM without AF. The levels of TNF-alpha, IL-6 in patients with AF and T2DM are comparable to the concentrations of these biomarkers of inflammation in patients with T2DM without AF. According to the results of echocardiography, it was revealed that the thickness of the epicardial adipose tissue in patients with AF and T2DM is greater than in patients with AF without T2DM and greater than in patients with T2DM without AF (7.1±0.4, 4.5±0.3 and 5.1±0.3, respectively, p˂0.001). A strong positive correlation between GDF-15 and HbA1c was established according to the correlation analysis (r=0.617, p˂0.0001) and regression analysis (β=0.586, p˂0.0001). According to binomial logistic regression, it was found that T2DM in the examined cohort increased the risk of AF by 2.2 times (OR=2.2, 95 %CI 1.41–3.31, p=0.00004).Conclusion. The obtained new data on the increase in the concentration of profibrogenic factors in patients with AF in combination with T2DM indicate an important role of the formation of myocardial fibrosis in the development of this arrhythmia in these patients.